2007
DOI: 10.1038/sj.bjc.6604021
|View full text |Cite
|
Sign up to set email alerts
|

Substituted titanocenes induce caspase-dependent apoptosis in human epidermoid carcinoma cells in vitro and exhibit antitumour activity in vivo

Abstract: Titanocene compounds are a novel series of agents that exhibit cytotoxic effects in a variety of human cancer cells in vitro and in vivo. In this study, the antiproliferative activity of two titanocenes (Titanocenes X and Y) was evaluated in human epidermoid cancer cells in vitro. Titanocenes X and Y induce apoptotic cell death in epidermoid cancer cells, with IC50 values that are comparable to cisplatin. Characterisation of the cell death pathway induced by titanocene compounds in A431 cells revealed that apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Since the precise mechanism underlying the observed changes in hTerT promoter activity in cancer cells is unclear, detailed investigations are needed. Here, cell cycle arrest at the S phase was demonstrated in Hela cells in response to cisplatin, in accordance with the results of other studies (22,23). it is known that telomerase synthesizes telomeres during the S phase, and that telomerase activity markedly increases during this phase of the cell cycle (24).…”
Section: Fold Induction Ddp (µG/ml)supporting
confidence: 79%
“…Since the precise mechanism underlying the observed changes in hTerT promoter activity in cancer cells is unclear, detailed investigations are needed. Here, cell cycle arrest at the S phase was demonstrated in Hela cells in response to cisplatin, in accordance with the results of other studies (22,23). it is known that telomerase synthesizes telomeres during the S phase, and that telomerase activity markedly increases during this phase of the cell cycle (24).…”
Section: Fold Induction Ddp (µG/ml)supporting
confidence: 79%
“…Bannon et al demonstrated cell cycle perturbation and late apoptotic A431 epidermoid carcinoma cell populations following exposure to cisplatin or titanocene Y (3; 50 µM; 48 h) 24 , indicative of caspase-induced apototosis. Similarly, gene expression analysis in small cell lung cancer cells treated with related species was in accord with DNA damage being the apoptosis trigger 25 .…”
Section: Cell Cycle Analyses γH2ax Foci and Apoptosismentioning
confidence: 99%
“…Since titanocene C exhibits a pattern of cytotoxicity different from cisplatin in a panel of cell lines, it is expected to constitute an interesting novel compound for treatment of SCLC which warrants further development. Finally, it should be mentioned that significant antitumor activity has been already reported for the class of titanocene compounds in experimental animal xenograft models [3,31].…”
Section: Discussionmentioning
confidence: 97%